Facile fabrication of raspberry-like composite microspheres for the construction of superhydrophobic films and applications in highly efficient oil–water separation. Issue 63 (14th August 2017) - Yu, Mingguang; Wang, Qing; Zhang, Min; Deng, Qianjun; Chen, Dongchu
Abstract : Inspired by the "lotus effect", we proposed a facile synthetic route toward raspberry-like PS@SiO2 microspheres, which further lead to superhydrophobic surfaces. Abstract : Inspired by the "lotus effect", we proposed a facile synthetic route toward raspberry-like PS@SiO2 microspheres, which further lead to superhydrophobic surfaces. In this approach, monodispersed polystyrene (PS) microspheres were first synthesized via dispersion polymerization using polyvinylpyrrolidone (PVP) as stabilizer. The obtained PS microspheres were then used as template microspheres for biomimetic silification using tetraethyl orthosilicate (TEOS) as precursor. Upon adjusting the molecular weight of PVP and the concentration of NH3 ·H2 O, the surface roughness of PS@SiO2 microspheres can be well controlled. Furthermore, after hydrophobization treatment, by drop-casting the raspberry-like PS@SiO2 microspheres onto a glass slide, dual-scale films were obtained, which had a similar surface morphology to that of the lotus leaf, exhibiting a water contact angle of 163.3° and water contact angle hysteresis of 4°. In addition, the oil–water separation ability of hydrophobic raspberry microsphere treated steel mesh was investigated. The results demonstrated excellent oil–water separation efficiency and reusability. This facile and robust synthesis technique for constructing a superhydrophobic surface hold great potential application in versatile and large-scale oil–water separation.